William Marshal Knight-Errant, Baron, and Regent of England - Painter, Sidney (Johns Hopkins University Press, 2020)
Originally published in 1933. As mediaeval society was dominated by the feudal caste, a biography that depicts the position, activities, manners, and thoughts of a member of that class might do much to elucidate the history of the period. This is what Sidney Painter had in mind when he wrote a William Marshal: Knight-Errant, Baron, and Regent of England. The subject has proved a peculiarly fortunate one. The fourth son of John fitz Gilbert, marshal of the king's court, William for the first forty years of his life was a landless knight who devoted most of his time and energy to tournaments. In the year 1189 by his marriage to the daughter and heiress of Earl Richard of Pembroke, William became a great feudal lord with fiefs in Normandy, England, Wales, and Ireland. Thus his biography depicts the two extremes of feudal society-the landless knight and the rich baron. Finally in 1216 he was chosen regent of England for the young king, Henry III, and his biography becomes for three years the history of England.